(untitled) (Research, Society and Development, 2021)
This article reflects the theme of Autistic Spectrum Disorder (ASD), a frequently discussed topic in the educational field, as it presents challenges for the inclusion of this public in the current society. Therefore, this research aims to review the literature on the contribution of educational electronic games in the development of students with ASD. As for the method, a systematic review was carried out, which consisted of analyzing papers published in Portuguese from 2012 to 2020 that addressed electronic games to help students with ASD in their educational development. In this perspective, a bibliographic survey was carried out through Google Scholar. For the selection of articles to be analyzed, some criteria were established in order to obtain data coherent with the research objective. From the analysis of the researched articles, the results revealed that, of 269 works, only 55 satisfied the criteria established for data organization, which were: to be from a case study; to thematize electronic games for students with ASD and to be capable of being used in class or at home. As a result, we found that in 2019 there was an increase in research in this subject and that the authors of the 55 selected articles used 20 electronic games accessible at school and at home with students with ASD, which proves the applicability of games as a learning strategy. Another fact drawn out of the data is that the games are played by students from the early years of elementary school, with an emphasis on literacy.